The Effect of Sales Growth and Asset Turnover on the Profitability of Agricultural and Fisheries Sector Companies Listed on the Indonesia Stock Exchange - Muh Rifai Arsyad; Haprila Putri Giantama; Abdur Rahman Hakim; Devita Aristya Sri Widya; Rahmi Aurya Bella; Windar Hidayati Lubis (Journal of Creative Power and Ambition (JCPA), 2026)
This study aims to examine the effect of Sales Growth and Total Asset Turnover on the profitability of agricultural and fisheries sector companies listed on the Indonesia Stock Exchange (IDX). The study employs a quantitative research approach using secondary data obtained from the annual financial reports of 20 companies during the 2024–2025 period, resulting in 40 observations. Data were analyzed using multiple linear regression with the assistance of IBM SPSS Statistics. Prior to hypothesis testing, descriptive statistics and classical assumption tests, including normality, multicollinearity, heteroscedasticity, and autocorrelation tests, were conducted to ensure the validity of the regression model. The results indicate that Sales Growth has a positive and statistically significant effect on profitability (β = 0.465; p < 0.001), while Total Asset Turnover also has a positive and statistically significant effect on profitability (β = 6.672; p< 0.001). Simultaneously, both independent variables significantly affect profitability (F = 63.758; p < 0.001). Furthermore, the coefficient of determination (R² = 0.775) shows that 77.5% of the variation in profitability can be explained by Sales Growth and Total Asset Turnover, while the remaining 22.5% is explained by other factors outside the model. These findings imply that improving sales performance and enhancing asset utilization efficiency are important strategies for increasing corporate profitability in the agricultural and fisheries sector.